The human bone manual - White, Timothy Douglas, 1950-; Folkens, Pieter Arend (Amsterdam : Elsevier academic press, 2005)
Building on the success of their previous book, White and Folkens' The Human Bone Manual is intended for use outisde the laboratory and classroom, by professional forensic scientists, anthropologists and researchers. The compact volume includes all the key information needed for identification purposes, including hundreds of photographs designed to show a maximum amount of anatomical information. * Features more than 500 color photographs and illustrations in a portable format; most in 1:1 ratio * Provides multiple views of every bone in the human body * Includes tips on identifying any human bone or tooth * Incorporates up-to-date references for further study
Includes bibliographical references (p. 429-452) and index.
Keywords: Forensic anthropology -- Handbooks, manuals, etc; Forensic osteology -- Handbooks, manuals, etc; Human remains (Archaeology) -- Handbooks, manuals, etc; Human skeleton -- Analysis -- Handbooks, manuals, etc; Human skeleton -- Classification -- Handbooks, manuals, etc; Human skeleton -- Identification -- Handbooks, manuals, etc